Our 9/11 of hope: Short essays on European democracy since 1989 - Fabrizio Tassinari (Danish Institute for International Studies (DIIS), 2010)
This collection of short essays proceeds from an international conference organized by DIIS on 9th November 2009, the day of the twentieth anniversary of the fall of the Berlin Wall. The volume centers on the political, social, and economic implications of the revolutions of 1989 on European democracy. The authors of these essays come from very different backgrounds and interests: ranging from academics and public intellectuals that have written extensively on post-Cold War Europe, to practitioners and activists who have witnessed or contributed in different capacities to the continent's democratic transformation. This diverse participation has enabled a broad discussion on existing paradigms of democratization and their record in Central and Eastern Europe; on the transition of former Communist states towards a market-based liberal democracy and the impact of events such as the 2009 economic crisis on it; on the role of the EU and of European integration. The volume is edited by Fabrizio Tassinari, Senior Researcher and Head of the Foreign Policy and EU Studies Unit and opens with a preface by Timothy Garton Ash. It includes articles by: Per Stig Møller, Bernd Henningsen, Balint Molnar, Morten Hansen, Michael Emerson, Arkady Moshes and Alyson JK Bailes.
Keywords: 300; Demokratie; Europäische Integration; Sozialer Wandel; Wirtschaftswachstum; Politik; EU-Staaten; Europa